Climate-smart practice: level of effectiveness and determinants of Sorjan farming adoption in coastal Bangladesh - Kundu, Nanda Dulal; Sujan, Md. Hayder Khan; Sarker, Mou Rani; Sultana, Monira; Uddin, Md. Taj; Bhandari, Humnath; Sarkar, Md Abdur Rouf (Springer, 2024)
Climate-smart agriculture stands as a promising solution to elevate cropping intensity and enhance food security in climate-vulnerable communities. Despite the evident potential, there is an existing gap in understanding the effects of climate change adaptation measures, with limited research explicitly focusing on adopting sorjan cultivation. This study seeks to address this gap by delving into the effectiveness and determinants of sorjan farming in the coastal regions of Bangladesh. Data was collected in three south-central districts, namely Patuakhali, Jhalakathi, and Pirojpur in 2022. A total of 222 farmers participated in the study, with 120 practicing plain land cultivation, while the remaining 102 were engaged in sorjan farming. Results show that the cropping intensity of farm households increased from 100–200% to 300–500% in sorjan farming. Farmers earned the highest net return by following the crop combinations of ‘Bottle gourd-Potato-Sweet gourd-Indian spinach’, ‘Banana-Okra-Snake gourd-Bottle gourd’, and ‘Jujube-Stem amaranth-Indian spinach’ under the sorjan method in Patuakhali, Jhalakathi, and Pirojpur districts, respectively. On average, farmers realized an additional net benefit of Tk. 55 for every Tk. 100 invested upon transitioning from plain land farming (benefit cost ratio, BCR = 1.25) to sorjan cultivation (BCR = 1.80). The results of the logit model found that household size, farming experience, and extension contact positively influenced the adoption of the sorjan method, while farmers' age and farm size had a negative influence. Further analysis of challenges in both types of farming revealed the advantages of sorjan over plain land cultivation, categorizing them into four distinct areas: environmental, management, input-related, and market issues. Government policies should prioritize holistic support systems and foster collaborative knowledge-sharing among stakeholders to enhance the adoption and diffusion of sorjan farming in coastal communities.